2005
DOI: 10.1256/qj.05.149
|View full text |Cite
|
Sign up to set email alerts
|

Convective‐scale assimilation of radar data: progress and challenges

Abstract: SUMMARYActive research has been carried out in recent years to assimilate high-resolution observations into numerical models to improve precipitation forecasting. Considerable progress has been made although great scientific and technological challenges still exist. This paper reviews techniques used in convective-scale data assimilation research. Experiences in the assimilation of radar observations into high-resolution numerical models are presented. A number of future challenges in convective-scale data ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
104
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(109 citation statements)
references
References 108 publications
1
104
0
4
Order By: Relevance
“…Research on data assimilation methods for models with kilometer-scale resolution (so-called cloudresolving, or cloud-permitting models) is still in its infancy (Sun, 2005), and many methods are being explored (Sun and Crook, 1998;Caya et al, 2005;Kawabata et al, 2007). The most common method in operational use at the time of writing is latent heat nudging (LHN: Jones and Macpherson, 1997;Leuenberger, 2005;Leuenberger and Rossa, 2007;Montmerle et al, 2007;Stephan et al, 2008;Dixon et al, 2009), although a variety of more advanced techniques have been studied in research contexts.…”
Section: Radar Data Assimilation: One Avenue To Improving Srnwp Qpfmentioning
confidence: 99%
“…Research on data assimilation methods for models with kilometer-scale resolution (so-called cloudresolving, or cloud-permitting models) is still in its infancy (Sun, 2005), and many methods are being explored (Sun and Crook, 1998;Caya et al, 2005;Kawabata et al, 2007). The most common method in operational use at the time of writing is latent heat nudging (LHN: Jones and Macpherson, 1997;Leuenberger, 2005;Leuenberger and Rossa, 2007;Montmerle et al, 2007;Stephan et al, 2008;Dixon et al, 2009), although a variety of more advanced techniques have been studied in research contexts.…”
Section: Radar Data Assimilation: One Avenue To Improving Srnwp Qpfmentioning
confidence: 99%
“…Since NWP models are sensitive to initial conditions, setting up accurate initial conditions is critical in short-term forecasting. Thus, additional quality control procedures are required for radar-data assimilation besides normal radar data quality control techniques (e.g., removing ground clutters, non-meteorological echoes, sun strobes) [10], while those high-quality data may not be available in an emergent situation [3]. Secondly, radar-only nowcasting requires significantly less computational resources than NWP models.…”
Section: Tropical Cyclone and Precipitation Nowcastingmentioning
confidence: 99%
“…To study the influences of variations in data assimilation cycle lengths on forecasts, and to implement shorter updating of model background states, HF radar data were temporally linearly interpolated onto intervals less than sixty minutes. The reasons for using temporally interpolated radar data are, firstly, Sun [45] suggested that it was desirable to have rapid update cycles to capture the temporal change and to obtain useful information from the model background states. The radar data were not regarded as a single snap-shot by Sun [45], but each point in the three-dimensional data volume was assimilated at the timestep closest to the measurement time in a sequential scan.…”
Section: Tests Of Data Assimilation Cycle Lengthsmentioning
confidence: 99%
“…The reasons for using temporally interpolated radar data are, firstly, Sun [45] suggested that it was desirable to have rapid update cycles to capture the temporal change and to obtain useful information from the model background states. The radar data were not regarded as a single snap-shot by Sun [45], but each point in the three-dimensional data volume was assimilated at the timestep closest to the measurement time in a sequential scan. Secondly, in operational data assimilation forecasting systems, measurements from different resources at different timesteps can be assimilated into models.…”
Section: Tests Of Data Assimilation Cycle Lengthsmentioning
confidence: 99%